2020
DOI: 10.1186/s12978-020-00987-8
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors and sex differences in condom non-use among adolescents: Brazilian National School Health Survey (PeNSE)

Abstract: Background Condom non-use among sexually active adolescents is a major cause of unintended pregnancy and sexually transmitted infections. In order to promote condom use, it is essential to understand factors associated with condom non-use. Aim Our aim was to evaluate sex differences and associated factors of condom non-use based on the nationally representative Brazilian National School Health Survey. Methods The study participants were 100,962 adolescents 13–18 years old, 9th graders from both public and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 44 publications
1
11
0
16
Order By: Relevance
“…Early initiation of sexual activity affects the sexual and reproductive health of the young population [ 5 , 13 ]. Youths who begin early sexual activity are more likely to have high-risk sex (multiple sexual partners) [ 8 ], and they are less likely to use condoms [ 14 ] which are related to the increased susceptibility to human immunodeficiency virus (HIV) and other sexually transmitted diseases (STDs) transmission, unwanted pregnancy, and its complications [ 5 , 6 , 9 , 11 , 13 , 15 – 19 ]. Worldwide, the high prevalence of teenage pregnancies among in-school adolescent girls in particular is a major concern for majority of parents, guardians, and duty bearers [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early initiation of sexual activity affects the sexual and reproductive health of the young population [ 5 , 13 ]. Youths who begin early sexual activity are more likely to have high-risk sex (multiple sexual partners) [ 8 ], and they are less likely to use condoms [ 14 ] which are related to the increased susceptibility to human immunodeficiency virus (HIV) and other sexually transmitted diseases (STDs) transmission, unwanted pregnancy, and its complications [ 5 , 6 , 9 , 11 , 13 , 15 – 19 ]. Worldwide, the high prevalence of teenage pregnancies among in-school adolescent girls in particular is a major concern for majority of parents, guardians, and duty bearers [ 20 – 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pesquisadora permaneceu no mesmo ambiente que o adolescente durante a coleta dos dados, para garantir que não houvesse dúvidas pelos participantes sobre o que se estava perguntando. Para a coleta de dados foi utilizado um instrumento desenvolvido e fundamentado nas diretrizes que orientam as boas práticas na realização de estudos observacionais (10) , com base nas experiências profissionais dos autores, e com base em publicações científicas nacionais e internacionais sobre a temática acerca dos fatores de risco (9) , práticas sexuais (11) e hábitos dos adolescentes (5,7,11) , e assim,…”
Section: Coleta De Dadosunclassified
“…O início precoce da vida sexual (prévio aos 15 anos), está relacionado a comportamentos sexuais de risco, expondo o adolescente a maiores chances de adquirir IST, ter mais parceiros sexuais, fazer uso inconsistente de métodos contraceptivos, engravidar sem desejar e fazer sexo com parcerias de risco. As práticas sexuais desprotegidas acarretam riscos para o adolescente como a aquisição de IST (5) e a gravidez na adolescência que representa um problema de saúde pública multidimensional. Com isso, é necessário compreender a multicausalidade envolvida na saúde sexual dos adolescentes para propor intervenções afinadas à realidade e sensíveis às suas especificidades (6) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Theme-Filha et al [23] found that, in Brazil, more than 50% of all pregnancies carried to term were unplanned and were associated with younger age, brown and yellow skin color, substance use, and lower education level. Students report not having received pregnancy prevention counseling or sexual health education [24]. Birth control methods reported by women of reproductive age include oral and/or injectable contraceptives, tubal ligation, and male condoms [25][26][27].…”
Section: Introductionmentioning
confidence: 99%